2013
DOI: 10.1021/jf402894x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Conjugated Silica Nanoparticles for Improving Bioavailability and Its Anticancer Applications

Abstract: Curcumin, a yellow bioactive component of Indian spice turmeric, is known to have a wide spectrum of biological applications. In spite of various astounding therapeutic properties, it lacks in bioavailability mainly due to its poor solubility in water. In this work, we have conjugated curcumin with silica nanoparticles to improve its aqueous solubility and hence to make it more bioavailable. Conjugation and loading of curcumin with silica nanoparticles was further examined with transmission electron microscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 34 publications
1
70
0
Order By: Relevance
“…Many efforts have been made to increase the water-dispersibility and bioavailability of curcumin, including encapsulation in liposomes (Dhule et al, 2012), cyclodextrins (Mohan et al, 2012), emulsions (Ahmed et al, 2012;Li, Ma, & Cui, 2014;Lin et al, 2009), solid lipid nanoparticles (Sun et al, 2013), polymer nanoparticles (Simion et al, 2013;Verderio et al, 2013), and inorganic nanoparticles (Gangwar et al, 2013;Jambhrunkar et al, 2014;Singh et al, 2013). Recently, there has been interest in utilizing biopolymer nanoparticles fabricated from proteins or polysaccharides to encapsulate curcumin, such as casein (Esmaili et al, 2011;Pan, Zhong, & Baek, 2013), chitosan (Yadav et al, 2012), and starch (Chin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been made to increase the water-dispersibility and bioavailability of curcumin, including encapsulation in liposomes (Dhule et al, 2012), cyclodextrins (Mohan et al, 2012), emulsions (Ahmed et al, 2012;Li, Ma, & Cui, 2014;Lin et al, 2009), solid lipid nanoparticles (Sun et al, 2013), polymer nanoparticles (Simion et al, 2013;Verderio et al, 2013), and inorganic nanoparticles (Gangwar et al, 2013;Jambhrunkar et al, 2014;Singh et al, 2013). Recently, there has been interest in utilizing biopolymer nanoparticles fabricated from proteins or polysaccharides to encapsulate curcumin, such as casein (Esmaili et al, 2011;Pan, Zhong, & Baek, 2013), chitosan (Yadav et al, 2012), and starch (Chin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are many examples of the preparation of drug-based sols using nanoparticles. The above mentioned curcumin was successfully stabilized in the aqueous sol by SiO 2 nanoparticles (the sol's stability is 100 times higher than in water) [47]; silica+curcumin composite has great promise in cancer therapy [48]. Our preliminary studies have shown that stability of the aqueous curcumin sols in the presence of cerium oxide nanoparticles also increases.…”
Section: The Hypothesis Assessment and Reviewmentioning
confidence: 82%
“…Silica nanoparticles conjugated to curcumin have recently been studied for efficacy in cervical cancer cells (Gangwar et al, 2013). Curcumin-loaded solid lipid nanoparticles (SLNs) have also been shown to display controlled release of the compund.…”
Section: Plga Nanoparticlesmentioning
confidence: 99%